Analisis Metode Pembelajaran Bahasa Arab Berbasis Higher Order Thinking Skills (HOTS) dalam Literatur Pendidikan - Husin, Malik (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
This study aims to analyze the implementation of Arabic language learning methods based on Higher Order Thinking Skills (HOTS) through literature studies to identify their effectiveness, challenges, and development strategies. Using a library research method with a qualitative approach, this study uses academic documents (journals, books, proceedings) in 2019-2024 as the subject, while the object is the HOTS concept and its application in Arabic language learning. Data collection techniques are carried out through systematic searches in academic databases with related keywords, then analyzed using content analysis through theme coding, pattern identification, and synthesis of findings. The results of the study indicate that the HOTS approach is effective in improving analytical, evaluation, and creative skills in Arabic language learning, especially through problem-based learning methods, flipped classrooms, and technology integration, despite facing obstacles such as limited teacher training and teaching materials. These findings recommend the development of a HOTS-based curriculum, intensive teacher training, and technology adaptation to optimize learning outcomes